Intellectual and Academic Functioning of School-Age Children With Single-Suture Craniosynostosis - Speltz, Matthew L. (Pediatrics, 2015)
OBJECTIVE: We compared the developmental status of school-age children with single-suture craniosynostosis (case group) and unaffected children (control group). Within the case group we compared the performance of children distinguished by location of suture fusion (sagittal, metopic, unicoronal, lambdoid). METHODS: We administered standardized tests of intelligence, reading, spelling, and math to 182 case participants and 183 control participants. This sample represented 70% of those tested during infancy before case participants had corrective surgery. RESULTS: After adjustment for demographics, case participants’ average scores were lower than those of control participants on all measures. The largest observed differences were in Full-Scale IQ and math computation, where case participants’ adjusted mean scores were 2.5 to 4 points lower than those of control participants (Ps ranged from .002 to .09). Adjusted mean case–control differences on other measures of achievement were modest, although case deficits became more pronounced after adjustment for participation in developmental interventions. Among case participants, 58% had no discernible learning problem (score <25th percentile on a standardized achievement test). Children with metopic, unicoronal, and lambdoid synostosis tended to score lower on most measures than did children with sagittal fusions (Ps ranged from <.001 to .82). CONCLUSIONS: The developmental delays observed among infants with single-suture craniosynostosis are partially evident at school age, as manifested by lower average scores than those of control participants on measures of IQ and math. However, case participants’ average scores were only slightly lower than those of control participants on reading and spelling measures, and the frequency of specific learning problems was comparable. Among case participants, those with unicoronal and lambdoid fusions appear to be the most neurodevelopmentally vulnerable.